CHALLENGES AND OPPORTUNITIES FOR PEDAGOGICAL SPECIALISTS IN SCHOOL EDUCATION: BEST PRACTICES FROM VARNA MUNICIPALITY - Hineva, Antoaneta (E-Journal VFU, 2025)
This article explores a selection of challenges and opportunities faced by pedagogical specialists in school education within Varna Municipality. It highlights examples of emerging opportunities through the exchange of best practices from Varna's educational system.The study includes an analysis of key factors such as the implementation of specific educational programs, the digitalization of education, financial incentives, and social benefits in thesecondary education system, all examined through the lens of contemporary research and good practices.
Keywords: challenges; new opportunities; teachers; 1:1 Model; innovations; motivation; Varna Municipality